Peptidylarginine deiminase-4 gene polymorphisms are associated with systemic lupus erythematosus and lupus nephritis. (4th March 2019) - Massarenti, L; Enevold, C; Damgaard, D; Ødum, N; Nielsen, CH; Jacobsen, S
Abstract : Objective : Peptidylarginine deiminase-4 (PAD4) is highly expressed by neutrophils and essential for citrullination occurring during the formation of neutrophil extracellular traps, which have been implicated in the pathogenesis of systemic lupus erythematosus (SLE) and lupus nephritis (LN). Single-nucleotide polymorphisms (SNPs) in PADI4 influence PAD4 expression and functionality. Here, we investigate whether SNPs in PADI4 influence the risk of SLE or LN. Method : Altogether, 234 SLE patients and 484 controls were genotyped for nine PADI4 SNPs known to alter PAD4 functionality and/or expression, or to be associated with other autoimmune diseases, using an in-house multiplex Luminex assay. All analyses were adjusted for age and gender. Results : Heterozygosity for rs1748033, and heterozygosity and homozygosity for rs1635564, were associated with increased occurrence of SLE [odds ratio (OR) 1.55, 95% confidence interval (CI) 1.08–2.23; OR 1.52, 95% CI 1.06–2.19; and OR 2.06, 95% CI 1.08–3.93, respectively]. Homozygosity for rs1635564 was also associated with increased occurrence of LN (OR 3.35, 95% CI 1.2–10.97). Notably, gene dose effects of the rs1635564 variant allele were observed for SLE (p = 0.005) and LN (p = 0.01). Carriage of minor alleles of five other SNPs (rs11203366, rs11203367, rs874881, rs2240340, and rs11203368) was associated with increased occurrence of LN and hypertension. Conclusion : The rs1635564 polymorphism of PADI4 is a candidate risk factor for SLE, particularly with renal involvement. Additional PADI4 polymorphisms also conferred increased risk of LN. Overall, these findings support the notion of PAD4 contributing to the pathogenesis of SLE and LN.